Knowledge and Perception of ‘Pay-to-Play’ in Football among Sport Journalists in Ghana - Appiah Kusi, Frank; Abieraba, Richard Samuel Kwadwo (Indonesian Journal of Sport Management, 2023)
Football (soccer) is a major sport among the Ghanaian population, followed by Boxing and other emerging sports like Handball, Indoor Volleyball, Swimming, Field Hockey, Basketball, Badminton, and Arm Wrestling, among others. To the Ghanaian community, ‘sports is football,’ and this has attracted much attention and interest among the youth in an attempt to develop their talent and skills. With such an interest and passion among the Ghanaian youth, it is an expectation and dire hope to be featured in football competitions. This often is not the case, as there is a perceived intention of ‘Pay-to-Play’ to participate in national football competitions in Ghana. This study explored the knowledge and perception of ‘Pay-to-Play’ in football among Sports Journalists in Accra, Kumasi, and Ho. The study adopted qualitative methods with a semi-structured open-ended question sent to the respondents via Email and WhatsApp. A purposive sampling technique was used to recruit the respondents, and the snowball technique aided the researchers in reaching other Sports Journalists. The study identified the existence of ‘Pay-to-Play’ in football in Ghana. This has resulted in the loss of interest in football consumption among the youth, particularly in the Ghana Premier League, and has led to less football development in Ghana.